Differentiating the second equation of the first system (segment AB) with respect to ξ and substituting the derivative di/dξ from the first equation, we arrive at the differential equation d2φ/dξ2=3/4*φ1/2.
Next, trying a solution of the form φ=(aξ-b)k and substituting into the previous differential equation, we obtain k=4 and a=+-1/4. Then imposing the boundary condition φB=0, we arrive at the solution φ=((ξ- ξB)/4)4.
Then i is easily calculated by differentiating the last equation with respect to ξ, substituting into the second equation of the first system (segment AB), and solving trivially for i.
The second system (segment BC) may be treated similarly.